Green Energy Planning of Cities and Communities: New Paradigms and Strategies for a Sustainable Approach. - Dall’O’, Giuliano (Springer, 2020)
In green planning, the correct management of energy in towns and cities is a critical issue and is the topic of this chapter. In the first part, a general overview is provided, identifying the new paradigms to be pursued according to the needs of reducing, and possibly eliminating, the emission of greenhouse gases and those gases that have an impact on the environment, also considering the technological evolution currently in progress and opportunities offered by the market of energy generation and management market. In the second part of the chapter, a methodological approach to Green Energy Planning on a territorial scale is proposed and discussed. The chapter is completed by an in-depth analysis of the European project which promotes an approach to bottom-up energy planning, the Covenant of Mayors: its methodologies are discussed and a case study is analysed.
Keywords: Nachhaltige Stadtentwicklung; Erneuerbare Energie; Dezentrale Energieversorgung; Energiekreislauf; Energieverteilung; Energiespeicherung; Bürgerenergie; Verkehrswende; Aktionsplan; Kommunaler Klimaschutz; Fallbeispiel